2021
DOI: 10.6007/ijarbss/v11-i13/8504
|View full text |Cite
|
Sign up to set email alerts
|

Hiking Tourism in Malaysia: Origins, Benefits and Post Covid-19 Transformations

Abstract: Recreational hiking tourism in ecotourism or nature-based sites is associated with a range of individual health effect outcomes. Although these outcomes have been extensively studied, there is little narration in the academic literature about the investigation on hiking. Hiking is one of the popular ecotourism activities in Malaysia that immerse with nature and is connected with health and wellness benefits. This paper review hiking tourism foundation, development and significant contributions in a growing arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The result revealed that health and wellbeing value and economic value is the most significant impact on satisfaction. Thus, this study proved that TNKT as ecotourism attractions offered more than merely the existing values which are understudied [5]. Ecotourism sites such as national parks play a key role in fostering wellbeing, boosting health and wellness through promoting ecotourism connectedness to the natural environment [34].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The result revealed that health and wellbeing value and economic value is the most significant impact on satisfaction. Thus, this study proved that TNKT as ecotourism attractions offered more than merely the existing values which are understudied [5]. Ecotourism sites such as national parks play a key role in fostering wellbeing, boosting health and wellness through promoting ecotourism connectedness to the natural environment [34].…”
Section: Discussionmentioning
confidence: 73%
“…Researchers argued that ecotourism is nature-based surroundings provide positive and valuable experiences and contribute to holistic wellness [4]. Ecotourists travel to enhance their wellness with more explicit recreational activities contributing to a healthier life [5]. It is in line with the Sustainable Development Goal 2030 agenda (SDG), where ecotourism embraces tourism for SDG, promoting beneficial and sustainable tourism and emphasising people's quality of life and wellbeing [1] [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the COVID-19 pandemic, many people have been searching for nature-based activities which they believe can improve physical and mental health (Calderón et al, 2022;Nordin & Jamal, 2021;Sia, 2020) after long movement control order periods implemented by governments starting from March 2020. This shows how important it is for travel organisations to utilise the full potential of nature-based tourism destinations in better showcasing their product.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, researchers have only focused on the health risk concerns associated with COVID-19 travel; few studies have been carried out on the benefits of alternative tourism. Recently, Nordin and Jamal [29] summarized the benefits of hiking tourism, which include improvements in quality of life and satisfaction, reductions in anxiety, and increased overall well-being of visitors. Wen et al [30] suggested that, after periods of overwhelming stress and outbreaks, the benefits of nature-based activities (hiking, trekking, wildlife observation, or nature interpretation) include being able to breathe fresh air and becoming connected with nature and rejuvenation.…”
Section: Covid-19 Tourism Researchmentioning
confidence: 99%